2011
DOI: 10.3109/09553002.2011.542542
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal tumours induced inApcMin/+mice by X-rays and neutrons

Abstract: X-ray or fission neutron irradiation results in strongly enhanced tumour multiplicities. Comparison of tumour yields indicated a low Relative Biological Effectiveness of around 2-8 for fission neutrons compared with X-rays. LOH in intestinal tumours from neutron-exposed mice appeared to be more complex than previously reported for tumours from X-irradiated mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The Min mice develop on an average 35 to 45 adenomas and these may appear as early as 60 days after birth. Others and we have reported that exposure of APC Min/+ mice to low-LET radiation causes significant increases in intestinal tumors relative to unirradiated controls [24]–[26]. We have also shown that 4 Gy 56 Fe radiation induced greater intestinal tumorigenesis than equitoxic 5 Gy γ irradiation in these mice [25].…”
Section: Introductionsupporting
confidence: 61%
“…The Min mice develop on an average 35 to 45 adenomas and these may appear as early as 60 days after birth. Others and we have reported that exposure of APC Min/+ mice to low-LET radiation causes significant increases in intestinal tumors relative to unirradiated controls [24]–[26]. We have also shown that 4 Gy 56 Fe radiation induced greater intestinal tumorigenesis than equitoxic 5 Gy γ irradiation in these mice [25].…”
Section: Introductionsupporting
confidence: 61%
“…Intriguingly, prior work has shown that radiation exposure increases the burden of intestinal tumor development in APC Min/+ mice in a dose-dependent manner, possibly through additional downstream effects on Wnt signaling. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological observations linking radiation and colorectal cancer (CRC) are also well supported by studies in animal models43536. Apart from carcinogenesis, radiation exposure has also been reported to cause metabolic and hormonal alterations related to growth and proliferation in human as well as in animal studies373839404142434445.…”
mentioning
confidence: 92%